A causal analysis of the role of institutions and organizational proficiencies on the innovation capability of Chinese SMEs. Issue 2 (April 2020) - Zhang, Man; Merchant, Hemant
Highlights: Guanxi and Government Support have a positive effect on Chinese SMEs' Improvisation and Learning capabilities. Improvisation and Learning capabilities have a positive effect on Chinese SMEs' Innovation capability. Guanxi 's effect on Improvisation is almost twice as much as its effect on Learning. Government Support 's effect on Learning is higher than its effect on Improvisation. Learning influences Innovation capability almost 3 times as much as Improvisation does. Abstract: We attempt to advance the existing narrative about the role of local institutions vis-à-vis the organizational capabilities of Chinese SMEs, and the influence of such linkages on the innovation capability of these firms. Specifically, we complement recent work by investigating the impact of macro- as well as micro-level aspects of Chinese institutions (Government support; Guanxi ) on the 'Improvisation' and 'Learning' capabilities of Chinese SMEs and, ultimately, these firms' innovation capability. Our conceptual arguments are embedded in Institutional, Organizational learning, and Resource-based theories. We isolate, unpack, and discuss several inter-related, yet distinct, causal mechanisms that ultimately influence Chinese SMEs' innovation capability development. Based on a Partial Least Squares analysis of more than 200 firms, we find empirical support for all six hypotheses which represent the above-mentioned relationships. Our findings offer insights pertaining to: (1) the relative impact of institutional versus firm-specific factors in developing organizational proficiencies, (2) the mapping of macro- and micro-level institutional effects on organizational proficiencies, and (3) the relative effect of organizational proficiencies on innovation performance.